Epigenome-wide DNA methylation signature of benzo[a]pyrene exposure and their mediation roles in benzo[a]pyrene-associated lung cancer development - Meng, Hua; Li, Guyanan; Wei, Wei; Bai, Yansen; Feng, Yue; Fu, Ming; Guan, Xin; Li, Mengying; Li, Hang; Wang, Chenming; Jie, Jiali; Wu, Xiulong; et al. (Journal of hazardous materials, 2021)
Benzo[a]pyrene (B[a]P) is a typical carcinogen associated with increased lung cancer risk, but the underlying mechanisms remain unclear. This study aimed to investigate epigenome-wide DNA methylation associated with B[a]P exposure and their mediation effects on B[a]P-lung cancer association in two lung cancer case-control studies of 462 subjects. Their plasma levels of benzo[a]pyrene diol epoxide-albumin (BPDE-Alb) adducts and genome-wide DNA methylations were separately detected in peripheral blood by using enzyme-linked immunosorbent assay (ELISA) and genome-wide methylation arrays. The epigenome-wide meta-analysis was performed to analyze the associations between BPDE-Alb adducts and DNA methylations. Mediation analysis was applied to assess effect of DNA methylation on the B[a]P-lung cancer association. We identified 15 CpGs associated with BPDE-Alb adducts (P−meta < 1.0 × 10−5), among which the methylation levels at five loci (cg06245338, cg24256211, cg15107887, cg02211741, and cg04354393 annotated to UBE2O, SAMD4A, ACBD6, DGKZ, and SLFN13, respectively) mediated a separate 38.5%, 29.2%, 41.5%, 47.7%, 56.5%, and a joint 58.2% of the association between BPDE-Alb adducts and lung cancer risk. Compared to the traditional factors [area under the curve (AUC) = 0.788], addition of these CpGs exerted improved discriminations for lung cancer, with AUC ranging 0.828–0.861. Our results highlight DNA methylation alterations as potential mediators in lung tumorigenesis induced by B[a]P exposure. [Display omitted] •We conducted the first epigenome-wide DNA methylation analysis of B[a]P exposure.•Exposure to B[a]P is significantly associated with methylation levels at 15 CpGs.•B[a]P-associated CpGs mediate 30~60% of its association with lung cancer.•DNA methylation plays a critical role in lung tumorigenesis induced by B[a]P.